Anti-browning Effect of Combined Calcium Lactate and Heat Treatment in Fresh-cut Organic Thai Eggplant cv. Chao Phraya - Krongyut, Wiraya; Chareekhot, Kasama; Auyyuenyong, Ratchada (AGRIVITA Journal of Agricultural Science, 2025)
Organic fresh-cut Thai eggplants cv. Chao Phraya were treated with 0.5% calcium lactate at ambient, 50°C or 60°C for 1 and 5 minutes before storage at 10°C with 90% relative humidity for 6 days. No calcium lactate treatment served as the control which turned brown very rapidly, reaching the browning limit of acceptability in less than one day. Calcium lactate at 50-60°C for 1 minute markedly slowed browning based on sensory scores, lightness (L*) values and brown pigment concentration. The treated eggplants had very slight browning symptoms after one day and reached the browning limit of acceptability after 4-5 days of storage. Correspondingly, the activities of polyphenol oxidase (PPO), peroxidase (POD) and phenylalanine ammonia lyase (PAL) were lowest while phenolics contents were highest among treatments. Prolonging the combined treatment duration to 5 minutes induced browning that was comparable to the control. Ambient calcium lactate treatment for 1 and 5 minutes had comparable intermediate responses in browning development and changes in phenolics content, PPO, POD and PAL activities. The treated fresh-cut eggplants reached the browning limit of acceptability in 2-3 days of storage.